ANALISIS POTENSI EKONOMI DAN KELAYAKAN INVESTASI USAHA KOPRA DI KABUPATEN GORONTALO - Nasaru, Yurni; Suparwata, Dewa Oka; Indrianti, Ayu; Djibran, Moh Muchlis (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2025)
ABSTRACT This study aims to analyze the economic potential and investment feasibility of copra business in Gorontalo Regency, using a SWOT analysis and financial analysis approach. The results of the financial analysis indicate that the business is feasible, with a Net Present Value (NPV) of IDR 63,167,388, an Internal Rate of Return (IRR) of 40%, and a Benefit-Cost Ratio (BCR) of 5.67. In the SWOT analysis, the key strength lies in the support from the local community and the availability of coconut raw materials, while the greatest weakness is the limited capital and dependence on the local market. Opportunities include technological advancements and partnerships with exporters, while the main Threats are fluctuations in copra prices and strict export-import regulations. The conclusion of this study recommends strategies to maximize local community support, utilize the latest technology to improve product quality and distribution, and establish partnerships with exporters to open access to global markets, which are expected to address existing challenges and support the sustainability of the copra business. Keywords: Economic Feasibility, SWOT Analysis, Copra Business, Latest Technology, Exporter Partnerships